A narrative review of studies addressing the clinical effectiveness of perinatal depression screening programs. Issue 1 (February 2020) - Reilly, Nicole; Kingston, Dawn; Loxton, Deborah; Talcevska, Kristina; Austin, Marie-Paule
Abstract: Background: Clinical practice guidelines recommend that women be screened for depression as a routine component of maternity care however there is ongoing debate about the benefits of depression screening programs in this context. Aim: This narrative review identifies and describes the clinical effectiveness of perinatal depression screening programs in relation to one or more of the following interrelated domains: referral for additional mental health support or treatment; engagement with mental health support or treatment options; and, maternal mental health or parenting outcomes. Methods: English-language studies, published up to July 2017, were identified and their methodological quality was assessed. RCTs and non-RCTs were included. Results: Overall, the majority of the fourteen studies identified showed that participation in a perinatal depression screening program increases referral rates and service use, and is associated with more optimal emotional health outcomes. One of four available studies demonstrated an improvement in parenting outcomes as a result of participation in an integrated postnatal depression screening program. Conclusion: This small but important body of work is integral to the continuing debate over the merits of screening for depression in the perinatal period. Current evidence favours the overall benefits of perinatal depression screening programs across the three focus areas of this review. Future research should consider a woman's broader psychosocial context and should address the economic as well as clinical outcomes of these programs. Rigorous evaluation of emerging digital approaches to perinatal depression screening is also required.